Job challenge profile : participant workbook - McCauley, Cynthia D. (Cynthia Denise), 1958- (Learning from work experience., 2019)
This updated Participant Workbook now includes the Job Challenge Profile survey. With the aid of this action guide, you will determine what and how much you are learning, what parts of your job holds key challenges, and what strategies you might adopt to derive maximal learning from these experiences.